Status of oxen traction research in ILRI, Ethiopia. Experiences and global prospective - Osuji, P.O.; Umunna, N.N.; Talle, S.B.; Yimegnuhal, A. (Ethiopian Agricultural Research Organization, 1998)
Draft oxen have been used extensively by smallholders in many crop-livestock mixed production systems. In these system, crop production is totally dependent on oxen power. Other livestock have also been used for draft purposes depending on locality and circumstances. However, improved efficiency of utilization of animal power is yet to be achieved necessitating more research on the effective utilization of animal power in small-scale agriculture. Studies by ILCA/ILRI on draft oxen have provided substantial information on draft power requirements, work output and effect of work and nutritional stress on animal performance and on the causes of fatigue. Additionally, strategies for the utilization of available feed resources for the dual purpose use of oxen for drought and beef have been evaluated. Nutrients needed by work oxen to optimize growth compensatory responses after a period of work have also been investigated. This paper Reports work carried out at the ILRI Debre Zeit Research Station on the effect of supplementation, body condition and work levels on the feed intake, live weight gain, carcass characteristics and physiological changes of Zebu draft animals. Specially, the effects of work on rectal temperature, respiration rate skin temperature and the effects of work and level of supplementation on blood metabolites are presented.